Persepsi dan Kepuasan Pengunjung Terhadap Keunikan dan Potensi Ekowisata Pesisir Kali Ciliwung - Pradini, Gagih; Kusumaningrum, Anisa Putri; Putri, Oktavika; Ardani, Putri Aulia; Karyatun, Subur (Peneliti.net, 2023)
Ciliwung River is located in an area that has a lot of tourism potential. This paper aims to examine visitors' perceptions and satisfaction of the uniqueness and potential of Ciliwung River coastal ecotourism. The coast of the Ciliwung River is an area that has interesting ecotourism potential, but is still not widely known by the public. This research is expected to provide a better understanding of visitor perceptions and satisfaction with the uniqueness and potential of Ciliwung River coastal ecotourism. The research method used is a qualitative method with descriptive analysis to identify visitor perceptions and satisfaction with the uniqueness and potential of Ciliwung River coastal ecotourism. Data collection techniques using interviews, observation, questionnaires, and documentation. The research results obtained are that the Ciliwung River is an enchanting place, displaying natural charm and its utilization for various human activities. The tourist attraction on the Ciliwung River is a tourist attraction in the form of natural charm with beautiful views and surrounded by greenery giving a natural feel, so that the tourist attraction on the Ciliwung River needs to be developed in a sustainable manner using the concept of ecotourism to attract tourists and improve the quality and sustainability of tourist attractions